2020
DOI: 10.1186/s13662-020-02699-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically almost periodic solutions for certain differential equations with piecewise constant arguments

Abstract: It is well known that differential equations with piecewise constant arguments is a class of functional differential equations, which has fascinated many scholars in recent years. These delay differential equations have been successfully applied to diverse models in real life, especially in biology, physics, economics, etc. In this work, we are interested in the existence and uniqueness of asymptotically almost periodic solution for certain differential equation with piecewise constant arguments. Due to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Yan et al ( 2022 ) revealed a broadband vibration energy harvester based on nonlinear magnetic force and rotary pendulums. Feng et al ( 2020 ) considered the almost periodic solutions for certain differential equations with piecewise constant arguments. Dai et al ( 2014 ) introduced a multi-parameter magnetoelectric response modeling of magnetostrictive laminate.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al ( 2022 ) revealed a broadband vibration energy harvester based on nonlinear magnetic force and rotary pendulums. Feng et al ( 2020 ) considered the almost periodic solutions for certain differential equations with piecewise constant arguments. Dai et al ( 2014 ) introduced a multi-parameter magnetoelectric response modeling of magnetostrictive laminate.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of these kinds of equations were initially mentioned in [20] and [5]. In the following years, qualitative properties such as the stability and convergence [32,34], oscillation [4,8], periodicity [4,6] of solutions of EPCA have been discussed deeply. Although the numerical study of EPCA starts late, it has gradually become more and more popular since EPCA can hardly be solved by analytical methods or much complicated to deal with.…”
mentioning
confidence: 99%